Health service gatekeepers - Malcomson, J (University of Oxford, 2003)
Incentive contracts for gatekeepers who control patient access to specialist medical services provide too weak incentives to investigate cost further when expected cost of treatment is greater than benefit. Making gatekeepers residual claimants with a fixed fee from which treatment costs must be met (as with full insurers who are themselves gatekeepers) provides too strong incentives when expected cost is less than benefit. Giving patients the choice between a gatekeeper with an incentive contract and one without is unstable. With one scenario, patients always prefer the latter. With another, patients have incentives to acquire information that makes incentive contracts ineffective.